2003
DOI: 10.1086/378359
|View full text |Cite
|
Sign up to set email alerts
|

Companions of Bright Barred Shapley-Ames Galaxies

Abstract: Companion galaxy environment for a subset of 78 bright and nearby barred galaxies from the Shapley Ames Catalog is presented. Among the spiral barred galaxies there are Seyfert galaxies, galaxies with circumnuclear structures, galaxies not associated with any large scale galaxy cloud structure, galaxies with peculiar disk morphology (crooked arms) and galaxies with normal disk morphology; the list includes all Hubbles types. The companion galaxy list includes the number of companion galaxies within 20 diameter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Condon (1987) shows a 45 mJy north-south source at 1.4 GHz, 54 00 resolution. Single-dish observations at 5 and 11 GHz (Garcia-Barreto et al 1993) show that this source is steep spectrum. Hummel (1980) establish an upper limit of 10 mJy to any core emission at 1.4 GHz, while the 15 GHz, 4 00 , and 0>2 resolution observations of Nagar et al (2000) give an upper limit of 1.3 mJy to any radio emission.…”
Section: Comments On Individual Galaxiesmentioning
confidence: 85%
See 1 more Smart Citation
“…Condon (1987) shows a 45 mJy north-south source at 1.4 GHz, 54 00 resolution. Single-dish observations at 5 and 11 GHz (Garcia-Barreto et al 1993) show that this source is steep spectrum. Hummel (1980) establish an upper limit of 10 mJy to any core emission at 1.4 GHz, while the 15 GHz, 4 00 , and 0>2 resolution observations of Nagar et al (2000) give an upper limit of 1.3 mJy to any radio emission.…”
Section: Comments On Individual Galaxiesmentioning
confidence: 85%
“…54 00 resolution, 1.4 GHz observations (Condon 1987) show a 21.3 mJy diffuse source. High-resolution observations at various frequencies (Heckman 1980;Hummel et al 1985;Garcia-Barreto et al 1993) show this object to harbor a flat-spectrum, et al (2000) give only upper limit of 1.3 mJy to any radio emission. NGC 4125.-There is no NVSS detection of this source.…”
Section: Comments On Individual Galaxiesmentioning
confidence: 95%
“…An intuitive explanation for NGC 3367 optical asymmetric morphology and large bipolar synchrotron emission might be a recent merger with a small galaxy since NGC 3367 has no large optical companion closer than 500 kpc (García-Barreto et al 2003). A gas rich galaxy may be a suited candidate because the asymmetric SF distribution.…”
Section: Evidence For Recent Ngc 3367mentioning
confidence: 99%
“…NGC 3367 is located in the field of the Leo Group but it belongs to the background based on its optical velocity of v o = 2998 km s −1 and the mean velocity of the Leo I Group = 900 km s −1 (Ferguson & Sandage 1990;Stocke et al 1991;Tonry et al 2001). The closest candidate for a galaxy companion is NGC 3391 at a projected distance of ∼ 563 kpc or 18 optical diameters away (García-Barreto et al 2003) and a recent search for isolated galaxies in the local universe based on the SDSS has also confirmed that NGC 3367 is an isolated galaxy (Hernández-Toledo et al 2010). The optical appearance of NGC 3367 is dominated by a bright bar and an apparent large-scale asymmetry or lopsidedness to the southwest side.…”
Section: Introductionmentioning
confidence: 99%
“…The angular resolution of the maps in Condon's (1987) atlas was insufficient to distinguish emission from the bar, the spiral arms and the halo. Another survey of barred galaxies in radio continuum by García-Barreto et al (1993) had even lower angular resolution; neither survey included polarization. The first high-resolution References: (1) Sandage & Tammann (1981); (2) de Vaucouleurs et al (1991); (3) Fullmer & Lonsdale (1989); (4) Condon (1987).…”
Section: Introductionmentioning
confidence: 99%